Hubungan Antara Merokok Dengan Kadar Kolesterol Total Pada Pegawai Pabrik Gula Tasikmadu Karanganyar - Kusumasari, Peni; , dr. Nur Hidayat, Sp. PD; , dr. Erika Diana Risanti (2015)
Background: Indonesia have become a country with a large number of smoker in the world and ranks fifth as consumer of cigarettes. People aged between 30 to 34 years are a largest proportion as active smoker which is 33,4 percent. Farmers/laborers/fishermen are the most active group of smoker based on job they have which is 44.5 percent. Smoking can lead to change of lipid concentrations in blood. Objective: In order to examine the relationship between smoking and total cholesterol level of employees of Tasikmadu karanganyar sugar factory. Methods: This research uses observational analytic method with cross sectional method. In order to test valuable relationship between those two variables, it uses Spearman correlation test. Research Result: 60 respondents who smoke and have high cholesterol levels are as much as 26 respondents (89.7%) meanwhile respondents who smoke and have desirable cholesterol levels are as much as 4 respondents (12.9%). Respondents who do not smoke and have desirable cholesterol level are as much as 27 respondents (87.1%). While respondents who do not smoke and have high cholesterol levels are as much as 3 respondents (10.3%). After analytical test is done with Spearmen correlation test, the result are p = 0,000 and r = 0.884 which means there is valuable correlation with very strong correlation level and positive correlation direction or unindirectional. Conclusion: There is a valuable relationship between smoking and total cholesterol level of employees of Tasikmadu Karanganyar Sugar Factory.